PENGARUH PENAMBAHAN UREA DAN MELAMIN PADA PEREKAT UREA FORMALDEHIDA TERHADAP EMISI FORMALDEHIDA DAN KETEGUHAN REKAT TRIPLEKS MERANTI - Paribotro Sutigno; Adi Santoso (Jurnal Penelitian Hasil Hutan (Journal of Forest Products Research), 2017)
The problem in using plywood bonded with urea formaldehyde (UF) is formaldehyde emission, especially in a room with limited ventilation. To reduce formaldehyde emission, the glue can be mixed with catching agent. In this paper the effect of urea and melamine as catching agent on formaldehyde emission and on bonding strength of UF bonded plywood made from red meranti (shorea. spp) is discussed.